High-intensity interval exercise performance in judo athletes: Physiological, perceptual, and pacing responses - Kons, R. L.; Detanico, D. (Motor control, 2022)
This study aimed to verify the behavior of physiological, perceptual, and performance responses during a high-intensity exercise in judo athletes and to identify if this protocol is able to discriminate athletes from different levels (national vs. state). Forty-five male judo athletes participated and were divided into two groups: state (age 24.2 ± 3.7 years) and national (22.1 ± 3.3 years). Judo athletes performed a judo-specific protocol contained high-intensity intermittent exercise consisted of 12 sets of 20 s in all-out intensity. During the protocol, the repetitions and heart rate were assessed over the sets, and at the end of the protocol, the rate of perceived exertion was measured. The results showed that the national group presented higher repetitions (29 ± 4 repetitions) during the high-intensity intermittent exercise compared with state (22 ± 2 repetitions). However, the national group showed a progressive decrease of repetitions up to the middle of the protocol, which coincided with higher values of heart rate compared with state (first and second sets). There was a decrease of repetitions from the first set (p < .001) and similar values of heart rate from the third set in the state. In conclusion, the performance (in repetitions) during the high-intensity intermittent exercise was able to discriminate athletes from different competitive levels. National athletes presented better performance, but worse pacing strategy compared with state.